2011
DOI: 10.1002/app.34552
|View full text |Cite
|
Sign up to set email alerts
|

Study on wettability improvement and its uniformity of wool fabric treated by atmospheric pressure plasma jet

Abstract: The influence of processing parameters on wettability improvement and its uniformity of wool fabric treated by atmospheric pressure plasma jet (APPJ) was explored. A woven wool fabric was treated by APPJ under various treatment conditions such as different treatment time, different oxygen flow rate, and different jet-to-substrate distance. The water absorption time of wool fabric was measured to determine wettability improvement. The diffusion photo of water droplet on wool fabric surface was taken by digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Although all fabric samples were of similar construction and showed similar WVP, water sorption and wettability differed significantly depending on the fibre type and finish. Untreated wool is known for its low water sorption and bad wettability; [38] as expected, the wool sample displayed the lowest water sorption value. In general, untreated PES is also hydrophobic with a wettability of >600 s. [39] In contrast to that, for our studies we chose a finished, hydrophilised PES material, typically used as first-layer clothing, which displayed a wettability of 118 s. The b-cyclodextrin finish increased WVP of all fabrics, but water sorption was considerably increased in WO, slightly increased in PES, and slightly decreased for CO. Wettability (i.e.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Although all fabric samples were of similar construction and showed similar WVP, water sorption and wettability differed significantly depending on the fibre type and finish. Untreated wool is known for its low water sorption and bad wettability; [38] as expected, the wool sample displayed the lowest water sorption value. In general, untreated PES is also hydrophobic with a wettability of >600 s. [39] In contrast to that, for our studies we chose a finished, hydrophilised PES material, typically used as first-layer clothing, which displayed a wettability of 118 s. The b-cyclodextrin finish increased WVP of all fabrics, but water sorption was considerably increased in WO, slightly increased in PES, and slightly decreased for CO. Wettability (i.e.…”
Section: Resultssupporting
confidence: 72%
“…Although all fabric samples were of similar construction and showed similar WVP, water sorption and wettability differed significantly depending on the fibre type and finish. Untreated wool is known for its low water sorption and bad wettability; as expected, the wool sample displayed the lowest water sorption value. In general, untreated PES is also hydrophobic with a wettability of >600 s .…”
Section: Resultssupporting
confidence: 68%
“…The application of APPJ on woven wool fabric showed a great wettability improvement and uniform plasma treatment. These effects decreased with the increasing oxygen flow rate and jet‐to‐substrate distance, and increased with the increasing of treatment time …”
Section: Hydrophilicitymentioning
confidence: 97%
“…It has been shown that plasma treatment using inorganic gas (such as argon, helium and oxygen) introduced new active sites on the surface and etched the fibre surface of the polyester and acrylic [42,43]. For wool fibres, partial removal of lipid layer and formation of cysteic acid after plasma was reported, which confers surface wettability and enhances the wicking properties of the fabrics [28,44,45]. Although sampling issues and visualisation of thin polymer films deposited on fibres using scanning electron microscopy are problematic, there was some evidence to suggest that silicon polymer is formed only on the fibre surface of the coated face (hydrophobic face).…”
Section: Discussionmentioning
confidence: 99%